IMPLEMENTING THE CHARACTER OF SITI MANGGOPOH STRUGGLE WITH THE NETHERLANDS AS A SOURCE OF HISTORICAL LEARNING - Muria Yuliana; Eka Nasha Putri D.Y (Indonesian Journal of Multidisciplinary Science, 2022)
The Manggopoh people's movement is a movement carried out by the Manggopoh people to address the people's anger and resistance to the policies implemented by the Dutch East Indies government, what's interesting about this movement is that the leader of the movement is a woman known as Mande Siti or Siti Manggopoh. This article aims to describe how Siti Manggopoh struggle against the Dutch. The data collected in the writing of this article were obtained through a literature review of a book entitled Siti Manggopoh. The troops led by Siti Manggopoh consisted of 17 people including Rasyid, the husband of Siti himself. From this movement gave birth to a battle and war of the Manggopoh people which greatly shocked the Minangkabau land at that time which matured 53 Dutch soldiers. because of the courage, religious obedience and love for the country which can be seen in the character of Siti Manggopoh struggle against the Netherlands, this can be used as a source of historical lessons.